1973
DOI: 10.1021/je60057a018
|View full text |Cite
|
Sign up to set email alerts
|

Heats of dilution of sodium chloride. Temperature dependence

Abstract: The heats of dilution of aqueous NaCI were measured over a concentration range of 0.1 -6.0m at 40°, 50°, 60°, 70°, and 80°C. The relative partial molal heat contents of solute and solvent were calculated from the experimental heats of dilution. These values were used to extend by calculation existing activity and osmotic coefficients to higher temperatures. These calculated values were found to be in excellent agreement with existing data. It is concluded that the use of heat of dilution data to correct existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 6 publications
(10 reference statements)
1
34
0
Order By: Relevance
“…Some slight adjustments of functional representations were necessary to obtain a more precise fit to the data. Equation (37) gives the Gibbs energy of the reference solution (m ) at r the reference pressure (P ) in terms of the empirically adjusted parameters r w 1 through w 5 . We use functions of inverse powers of (T-227) and (680-T) which were chosen by Rogers and Pitzer [1] to represent the relatively extreme behavior near 0°C and near the critical point of water.…”
Section: -· 43 Temperature Dependence Of Parameters and Weighting Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Some slight adjustments of functional representations were necessary to obtain a more precise fit to the data. Equation (37) gives the Gibbs energy of the reference solution (m ) at r the reference pressure (P ) in terms of the empirically adjusted parameters r w 1 through w 5 . We use functions of inverse powers of (T-227) and (680-T) which were chosen by Rogers and Pitzer [1] to represent the relatively extreme behavior near 0°C and near the critical point of water.…”
Section: -· 43 Temperature Dependence Of Parameters and Weighting Ofmentioning
confidence: 99%
“…While all of the results of this study are included, implicitly, in the preceding equations (37) through (40), it is convenient to combine these equations with those of Rogers and Pitzer [1] for the pressure dependence of the various functions. Since the same series of temperature dependent terms are used for the pressuredependence as for the parent functions, some numerical coefficients may be combined.…”
Section: Equations Including Pressure Dependencementioning
confidence: 99%
“…A comparison between calculated and literature data (Ensor and Anderson, 1973;Harned and Owen, 1958) shows that in the temperature range 293-373 K, the Pitzer model, along with the temperature dependence of B#&, B t i and CtX proposed by Pitzer et al (1984), gives the best fit of the activity coefficients of NaCl: standard deviation of 0.004 with a maximum deviation occurring at 373 K (s.d. 0.009).…”
Section: Application Of the Pitzer Model To The Naci-kci Aqueous Systemmentioning
confidence: 86%
“…A similar equation was also fitted to the NaCl data shown in Appendix A (Table A-1). 1 5 ' 16 The results demonstrated that the NaCI osmotic pressures were about 10% greater than the osmotic pressure=• exerted by standard sea-salt solutions at the same temperature and TDS weight concentration, or n (NaCl) -1.10 -r (sea salt) .…”
Section: Mass-transport Equations and Materials Balancesmentioning
confidence: 91%